Power stability control of wind-PV-battery AC microgrid based on two-parameters fuzzy VSG - Zhou, Wenwei; Wang, Binjie; Gu, Jipeng; Zhang, Youbing; Wang, Shuyi; Wu, Yixuan (Frontiers in Energy Research, 2023)
Virtual synchronous generator (VSG) control addresses the issue of decreasing microgrid standby inertia caused by the rise in wind turbines and photovoltaic (PV) penetration. However, various types of perturbations occur frequently making the traditional constant parameter VSG control unable to meet the system performance requirements, and thus a two-parameters fuzzy VSG control is proposed to ensure that microgrid inertia and damping. Firstly, the device-level control of each generation unit in the microgrid is designed based on the wind-PV-battery alternating current (AC) microgrid architecture. Secondly, fuzzy VSG control uses fuzzy rules written in plain language to represent the relationship between the main VSG factors and the power and frequency. Then, the influence of virtual inertia and damping coefficient on the dynamic performance of the system is analyzed through the theory of small-signal model, and a reasonable variation range of VSG parameters are given. Finally, the simulation model of wind-PV-battery AC microgrid is built in MATLAB/Simulink, and compared with other improved VSG control strategies, the fuzzy VSG control proposed in this paper has better dynamic performance and safety stability. This research emphasizes the practicality and importance of utilizing fuzzy control to adjust VSG techniques for developing microgrid configurations incorporating more renewable energy sources to guarantee the reliability and efficiency of microgrid.